Controle supervisório aplicado a sistemas fotovoltaicos autônomos com topologia multi string - Cândido, Diogo Brum (2010)
This master thesis analyses and implements a stand-alone photovoltaic system based on decentralized Multi String topology. The proposed system is composed of a set of DCDC converters linked to the PV arrays of panels, a bidirectional converter to perform the control of the charge/discharge process of the battery bank and ensure the specifications of DC link and a full-bridge inverter that feed the AC loads. Therefore, all operation modes that the stand-alone PV system can work are presented and analyzed. As the chief aim is to ensure the energy balance of the stand-alone PV system, are presented independents control loops for each converter of the PV system and a propose of a supervisory control that, based on information about the conditions of the DC link and the bank of batteries, defines each operation mode should be active, in order to maximize the power extracted from the PV arrays, the life cycle of the battery bank and ensuring the uninterrupted feeding of energy to the loads. Finally, simulation and experimental results validate the operation of the proposed system under different load and solar radiation conditions.